High-velocity projectile penetration test and theoretical calculation of pseudo fluid penetration of calcareous sand - Wei Guo; Yanyu Qiu; Mingyang Wang (Defence Technology)
To explore the penetration resistance of calcareous sand media, penetration tests have been conducted in the velocity range of 200–1000 m/s using conical-nosed projectiles with a diameter of 14.5 mm. Further, a pseudo fluid penetration model applicable to the penetration of rigid projectiles in sand media is established according to the approximate flow of compacted sand in the adjacent zone of penetration. The correlation between the impedance function of projectile-target interaction and the internal friction features of pseudo fluid is clarified, and the effects of sand density, cone angle of nose-shaped projectile, and dynamic hardness on the penetration depth are investigated. The results verify the feasibility, wide applicability, and much lower error (with respect to the experimental data) of the proposed model as compared to the Slepyan hydrodynamic model.